A critical review on performance and phase separation of thermosetting epoxy asphalt binders and bond coats. (4th April 2022) - Xie, Hongfeng; Li, Chenxuan; Wang, Qingjun
Highlights: Performance of epoxy asphalt binders and bond coats during and after curing is reviewed. Phase separation evolution and final phase-separated morphology of epoxy asphatls are discussed. The effect of additives on the properties and phase separation of epoxy asphalts is addressed. Difference between thermoplastic and thermosetting polymer modified asphalts is compared. The future outlooks of epoxy asphalts is highlighted. Abstract: Epoxy asphalt is a unique representative of thermosetting polymer modified asphalt, which has been widely used in the construction of orthotropic steel deck bridges. This paper reviewed the performance and phase separation of epoxy asphalt binders and bond coats. To well understand the characteristics of the main components of epoxy asphalts, epoxy resin and asphalt were introduced. The history and classification of epoxy asphalt were described. The importance of viscosity-curing time behavior for controlling the allowable construction time of epoxy asphalt mixtures was discussed due to the reactive nature of epoxy asphalt binders. The factors that affect the mechanical and bonding properties and thermal stability of epoxy asphalt were analyzed. Cure behaviors of epoxy asphalts characterized by different models of differential scanning calorimetry (DSC) were compared. The relationship between dynamic shear rheometry (DSR) and dynamic mechanical analysis (DMA) for studying the viscoelastic properties of epoxy asphalt was interpreted. The two glass transitions, damping properties and Cole-Cole plots of epoxy asphalt obtained by DMA were reviewed. Although scanning electron microscopy (SEM) and fluorescence microscopy (FM) can be used to observe the phase-separated microstructures of epoxy asphalts to some extent, there were still some disadvantages, such as the inability for observation of phase separation evolution, difficulty in sample preparation and low contrast and resolution. The principle of laser scanning confocal microscopy (LSCM) with high image resolution and contrast was introduced. The phase separation mechanism of epoxy asphalt and polymer modified epoxy asphalts was compared. Influence of phase-separated morphology on the mechanical properties of cured epoxy asphalts and polymer modified epoxy asphalts was analyzed.